Analisis pengaruh parameter proses terhadap kuat tarik produk 3D Printing dari bahan Polyvinyl Alcohol (PVA) - Aris Widyo Nugroho; Dede Tohidin; Cahyo Budiyantoro (Universitas Muhammadiyah Metro, 2020)
Polyvinylalcohol (PVA) is a polymer that is often used in 3D printing technology in the health sector. However, most research addresses the behavior of products interacting with the body, and very rare information discus about the mechanical properties of 3DP products from PVA. This study aims to determine the effect of 3D printing process parameters on PVA materials using the Taguchi method. PVA filament with diameter of 1.75 mm was obtained from ESun Co. Specimen was designed with CAD according to ASTM D-638 Type IV and fabricated using Pursa-I3 3D Printer Machine. The orthogonal arrays L4 (22) experimental design with two process parameters namely nozzle temperature and extrusion width and two levels for each parameter with tensile strength in response was carried out. The specimen was then measured by weight, dimensions, and time of production. After that the specimens were tested using the Zwick Roell Z020 engine. The data were then analyzed using S/N Ratio and ANOVA. The results showed that all the products meet the dimensions that have been set with the product weight that is not much different (0.03-0.1 gr). S/N Ratio and ANOVA analysis showed the same results that the extrusion width parameter had a greater effect than the temperature of the nozzle on the tensile strength response of the PVA product. The combination of optimal process parameter levels obtained, nozzle temperature of 180 ° C and extrusion width of 0.4 mm produces the highest tensile strength of PVA products (7,611 MPa).Keywords : 3D Printing, PVA, Taguchi, tensile strength.